Excited-state intramolecular proton transfer (ESIPT)-based fluorescent probes for biomarker detection: design, mechanism, and application. Issue 15 (1st February 2023) - Gu, Hao; Wang, Wenjing; Wu, Wenyan; Wang, Maolin; Liu, Yongrong; Jiao, Yanjun; Wang, Fan; Wang, Fang; Chen, Xiaoqiang
Abstract : Biomarkers are essential in biology, physiology, and pharmacology; thus, their detection is of extensive importance. Abstract : Biomarkers are essential in biology, physiology, and pharmacology; thus, their detection is of extensive importance. Fluorescent probes provide effective tools for detecting biomarkers exactly. Excited state intramolecular proton transfer (ESIPT), one of the significant photophysical processes that possesses specific photoisomerization between Keto and Enol forms, can effectively avoid annoying interference from the background with a large Stokes shift. Hence, ESIPT is an excellent choice for biomarker monitoring. Based on the ESIPT process, abundant probes were designed and synthesized using three major design methods. In this review, we conclude probes for 14 kinds of biomarkers based on ESIPT explored in the past five years, summarize these general design methods, and highlight their application for biomarker detection in vitro or in vivo .